2009
DOI: 10.1182/blood-2009-05-220327
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant canine B-domain–deleted FVIII exhibits high specific activity and is safe in the canine hemophilia A model

Abstract: Production of recombinant B-domaindeleted canine factor VIII (cFVIII-BDD) unexpectedly revealed superior protein yields with 3-fold increased specific activity relative to human FVIII-BDD (hFVIII-BDD). We also determined that activated cFVIII-BDD is more stable than activated hFVIII-BDD. Furthermore, cFVIII-BDD is efficient at inducing hemostasis in human plasma containing FVIII inhibitors. Infusion of cFVIII-BDD in hemophilia IntroductionHemophilia A (HA) is an X-linked bleeding disease resulting from a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(113 citation statements)
references
References 24 publications
(24 reference statements)
5
108
0
Order By: Relevance
“…17 Levels of hBF8 and IR8 in plasma and platelets of both transgenic and bone marrow reconstituted mice were determined using an anti-human specific enzyme linked immunosorbent assay (ELISA) kit (Affinity Biologicals) compared with recombinant full-length hF8 protein (Baxter Health Corporation). cBF8 levels were detected using a cF8-specific ELISA as described 24 compared with purified recombinant cBF8 protein. 24 Total pF8 determinations were done on platelet releasate after 3 cycles of freeze/thaw at Ϫ80°C/37°C of the platelet pellet.…”
Section: Determination Of F8 Antigenic and Functional Levelsmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Levels of hBF8 and IR8 in plasma and platelets of both transgenic and bone marrow reconstituted mice were determined using an anti-human specific enzyme linked immunosorbent assay (ELISA) kit (Affinity Biologicals) compared with recombinant full-length hF8 protein (Baxter Health Corporation). cBF8 levels were detected using a cF8-specific ELISA as described 24 compared with purified recombinant cBF8 protein. 24 Total pF8 determinations were done on platelet releasate after 3 cycles of freeze/thaw at Ϫ80°C/37°C of the platelet pellet.…”
Section: Determination Of F8 Antigenic and Functional Levelsmentioning
confidence: 99%
“…cBF8 levels were detected using a cF8-specific ELISA as described 24 compared with purified recombinant cBF8 protein. 24 Total pF8 determinations were done on platelet releasate after 3 cycles of freeze/thaw at Ϫ80°C/37°C of the platelet pellet. For platelet-releasate F8 determination, platelets were incubated at 37°C with thrombin (final concentration, 1 U/mL; Sigma-Aldrich) for 10 minutes.…”
Section: Determination Of F8 Antigenic and Functional Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ishiwata and colleagues have been treated hemophilia mice using AAV8 vector containing canine BDD -FVIII gene (Ishiwata et al, 2009). Sabatino and colleagues report indicated that canine BDD-FVIII dogs is stable than human BDD-FVIII, it can be considered in the hemophilia treatment (Sabatino et al, 2009). Doering et al were transferred hFVIII -sFVIII hybrid in to hematopoietic stem cells with lentiviral vector; cells expressed FVIII more than 100-8 times of cells transfected with hFVIII only (Doering et al, 2009).…”
Section: Gene Therapy Of Hemophilia Amentioning
confidence: 99%